2010
DOI: 10.1038/onc.2010.335
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose paclitaxel synergizes with oncolytic adenoviruses via mitotic slippage and apoptosis in ovarian cancer

Abstract: The microtubule-stabilizing drug paclitaxel has activity in relapsed ovarian cancer. dl922-947, an oncolytic adenovirus with a 24-bp deletion in E1A CR2, replicates selectively within and lyses cells with a dysregulated Rb pathway and has efficacy in ovarian cancer. In the aggressive A2780CP xenograft, combination treatment with weekly dl922-947 and paclitaxel has significantly greater efficacy than either treatment alone and can produce complete tumor eradication in some animals. We investigated the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Spread relies both upon release of virus from initially infected cells as well as upon subsequent infection of neighboring cells. Although adenovirus release is largely lytic, we have recently shown that a nonlytic mechanism may exist, dependent upon stabilized microtubules (42). The in vitro experiments described here lasted for 5 days at most, which allowed approximately 2-3 rounds of replication (43).…”
Section: Figurementioning
confidence: 99%
“…Spread relies both upon release of virus from initially infected cells as well as upon subsequent infection of neighboring cells. Although adenovirus release is largely lytic, we have recently shown that a nonlytic mechanism may exist, dependent upon stabilized microtubules (42). The in vitro experiments described here lasted for 5 days at most, which allowed approximately 2-3 rounds of replication (43).…”
Section: Figurementioning
confidence: 99%
“…1 Here we choose the combination of chemotherapy rather than radiotherapy and adenovirus is intended to explore a new way of topical chemotherapy plus topical injection of oncolytic virus to treat uveal melanoma. Next, some studies of the described combination treatment for other tumor type observed an augmentation of apoptosis [12][13][14][15] while our investigation demonstrated that whether monotherapy of DTIC or H101, or co-treatment appears to be related to cell cycle blocking instead of apoptosis. Meanwhile we observed DTIC did not enhance the killing ability of H101 through upregulation of cell entry or virus replication.…”
Section: Discussionmentioning
confidence: 97%
“…A synergistic tumor cell killing ability has been previously observed in the combination therapy of various adenoviruses with chemicals due to the augmentation of apoptosis. [12][13][14][15] Chemotherapy, which is mediated by a different mechanism, often induces distinct toxicity and causes multiple side effects, whereas oncolytic adenovirus exhibits greater tumor selectivity. Thus, in combination they potentially act synergistically without overlapping toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A modest response of dl922-947 was also reported in combination with gemcitabine in pancreatic cancer cells compared with trials using the virus alone (25,26). The microtubule-stabilizing drug paclitaxel (PTX) exhibits activity in relapsed cancer and regimes containing a weekly low-dose PTX are highly effective (27).…”
Section: Introductionmentioning
confidence: 99%